Description Of Mothers' Knowledge Regarding Providing Complementary Foods (Mp-Asi) To Infants Aged 6-12 Months At Posyandu X Koja Village, North Jakarta - Ana Silvera; Roza Indra Yeni; Ricky Riyanto Iksan; Reghula Maryeti Sandra (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2025)
Background: Breastfeeding (MP-ASI) is an important stage in meeting the nutritional needs of infants aged 6-12 months. Mothers' knowledge about MP-ASI influences the timing, type, texture, and frequency of feeding. Lack of knowledge can lead to inappropriate MP-ASI feeding, thus endangering infant growth and development. The purpose : of this study was to determine the overview of mothers' knowledge about MP-ASI administration for infants aged 6-12 months at Posyandu X, Koja Village, North Jakarta. This research method: used a quantitative descriptive design with a total sampling technique. Data were collected through questionnaires that had been tested for validity and reliability, then analyzed using univariate analysis. The results: of this study showed that most respondents were aged 20-35 years (84.9%), had secondary education (53.5%), and worked as housewives (80.2%). A total of 44 respondents (51.2%) had poor knowledge about MP-ASI administration and 42 respondents (48.8%) had good knowledge. The conclusion: of this study is that the majority of mothers have poor knowledge about MP-ASI administration. Ongoing education is needed to improve mothers' understanding of appropriate complementary feeding (MP-ASI) to support optimal infant growth and development